Switching Free Users to Paid Users: How to Increase Purchase Intention In Edtech Industry - Senalasari, Widi; Amelia, Putri (Politeknik Negeri Bengkalis, 2023)
Even though Indonesia has made significant gains in recent years to increase access to education, learning outcomes remain inadequate. However, the Edtech industry began to develop and increase educational output as a result of increasing access to education through technology. This growth, however, is in risk of becoming unsustainable because not every Edtech is profitable enough to thrive. This study aims to understand the buying interest factors of online course users by investigating the relationship between learning oriented related cues (perceive lecturer expertise, personal learning experience, personal trial experience), price value with purchase intention through customers trust and customers performance expectations. The data was gathered through an e-questionnaire issued to 414 respondents who had previously used a free trial of an online learning course, as well as through in-depth interviews with representatives of Edtech and content creator marketing. The result of this study shows significant and positive relationship between all variables in proposed model. The findings of this study are likely to assist marketers in increasing the number of free users who switch to paid users through content marketing that highlighted various indicators that matter to customers.